Blockchain-enabled smart contracts for enhancing seed certification transparency: A design science approach - Deo Shao; Nyankomo Marwa (Smart Agricultural Technology, 2024)
Context: Achieving zero hunger through food security, improved nutrition, and sustainable agriculture is one of the global agendas. Thus, the quality of seeds is important for ensuring sustainable food security, making seed certification critically important. However, classical seed certification systems are predominantly paper-based with limited digitisation. These systems, even digitised, are often centralised, and they face challenges related to transparency, traceability, and integrity. Objective: This study aims to investigate the practicality of blockchain technology in revitalising transparency, traceability, and integrity in the seed certification process. Methods: This study used a Design Science Research (DSR) approach to design and test a blockchain-based smart contract to improve the seed certification process. Within the DSR framework, the study used literature review and evolutionary prototyping to establish the requirements and design the prototype. Results and conclusions: The findings demonstrate the practical application of blockchain technology in improving aspects of transparency and integrity in the seed certification process. The findings further underscore that smart contracts can be leveraged efficiently to automate and enhance the seed certification process. The findings provide evidence-based frameworks for decision-makers and practitioners to justify the prioritisation of blockchain technology in designing future sustainable agricultural systems. Future studies should investigate how blockchain-based systems for seed certification can be scaled and integrated with existing agricultural systems. Significance: This study provides both theoretical and practical contributions on application of blockchain technology in the domain of seed supply chain. Specifically, it provides a comprehensive account of the design aspects of blockchain system in the seed certification process.